AGRARIAN REFORM AND CHANGES IN THE CULTURAL HERITAGE LANDSCAPE OF RURAL LATGALE IN 1920S AND 1930S - Malahovskis, Vladislavs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In the 20th century, Latvia underwent several rapid rearrangements of social and economic system. One of them were the Latvian Agrarian Reform (1920–1937) due to the implementation of which also the Latgalian rural cultural heritage landscape changed. In Latgale, there were established farmsteads instead of compactly inhabited locations (villages, in Latvian – sādžas). The rural landscape of Latgale became similar to rural landscape in other regions of Latvia. The aim of the article is, studying the economic and social aspects of life in Latgalian villages, to find out the outcomes of dividing villages into farmsteads during the Latvian Agrarian Reform, their influence on changes in the Latgalian rural cultural heritage landscape.